2007
DOI: 10.1007/s00436-007-0784-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and enzymatic activities of four protein disulfide isomerase (PDI) isoforms of Leishmania amazonensis

Abstract: Leishmania parasites primarily infect cells of macrophage lineage and can cause leishmaniasis in the skin, mucosal, and visceral organs, depending on both host-and parasite-derived factors. The protein disulfide isomerases (PDIs) are thiol-disulfide oxidoreductases that catalyze the formation, reduction, and isomerization of disulfide bonds of proteins in cells. Although four Leishmania PDI genes are functionally inferred from homology in the genome sequences, only two of them have been expressed as active pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…Surprisingly, despite a high degree of homology with LmPDI (86% of identities and 96% of similarities), the 52-kDa L. amazonensis PDI protein displayed only the isomerase activity (Hong and Soong 2008). Moreover, in another Trypanosomatidae (T. brucei), the LmPDI orthologue, Td-PDI-2 also displays only the isomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, despite a high degree of homology with LmPDI (86% of identities and 96% of similarities), the 52-kDa L. amazonensis PDI protein displayed only the isomerase activity (Hong and Soong 2008). Moreover, in another Trypanosomatidae (T. brucei), the LmPDI orthologue, Td-PDI-2 also displays only the isomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Four L. amazonensis PDIs encoding 52-, 47-, 40-, and 15 kDa proteins have been characterized. Homology analysis showed that the sequence identity between L. amazonensis (New World) PDIs and their counterpart PDI sequences from L. major (Old World) ranged from 76% to 99% [16]. Meek et al 2002 have detected IgG specific to four LaPDIs (especially to the 52 kDa PDI, known as PDI-2) [17].…”
Section: Protein Overexpression and Purificationmentioning
confidence: 99%
“…Taken together, these results demonstrate that the recombinant LtPDI-His is able to catalyze both oxidation and isomerization of protein disulfides. In a previous another study, Hong and Soong 2008 showed that the L. amazonensis 15, 40, and 47 kDa PDIs display both isomerase and reductase activities. Surprisingly, despite a high degree of homology with Lm PDI (86% of identities and 96% of similarities), the 52 kDa L. amazonensis PDI protein displayed only the isomerase activity [16].…”
Section: Pdi-2-stimulated Oxidation and Disulfide Bond Isomerization mentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that PDIs are also involved in a wide range of other biological functions in many cellular compartments including the cell surface, where they may participate in the reducing exterior environment and/or may be involved in cell adhesion (Turano et al, 2002). Parasite PDI-like enzymes were identified in Neospora caninum (Naguleswaran et al, 2005), Toxoplasma gondii (Meek et al, 2002a,b), Theileria parva (Ebel et al, 2002), different Leishmania species (Hong and Soong, 2008;Ben et al, 2002;Padilla et al, 2003), Cryptosporidium parvum (Blunt et al, 1996) and several species of Plasmodium (Florent et al, 2000;Mahajan et al, 2006;Mouray et al, 2007;Novo et al, 2009). T. gondii and N. caninum, both closely related to B. besnoiti (Ellis et al, 2000), have been shown to express highly homologous molecules, which could indicate that PDI plays a key role in the biology of neosporosis and toxoplasmosis (Ma et al, 2009;Meek et al, 2002a;Naguleswaran et al, 2005).…”
Section: Introductionmentioning
confidence: 99%